The Analysis of Students’ English Skill Needs in the Hotel Management Study Program at SMK Negeri Kesehatan dan Pariwisata Bangkinang - Dzulhijjah Yetti; Rahmad Akbar; Hayatul Khairul Rahmat; Andri Nofiar Am (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
This study investigates the English language skill needs of students enrolled in the Hotel Management Study Program (HMSP) at SMK Negeri Kesehatan dan Pariwisata Bangkinang, Riau Province, Indonesia. Grounded in the English for Specific Purposes (ESP) framework, the research adopts a descriptive qualitative design; data were collected through structured questionnaires, semi-structured interviews, and non-participant classroom observations. Findings reveal that speaking and listening are the most critical competencies for students who will serve as front-line hospitality professionals, particularly in guest-interaction scenarios such as handling reservations, managing complaints, and delivering hotel information. Three principal challenges were identified: difficulties with accent comprehension and pronunciation, limited industry-specific vocabulary, and communication anxiety. These results carry direct implications for ESP curriculum design in vocational secondary schools: learning materials and classroom activities should be systematically aligned with authentic hospitality communication contexts, including role-play simulations grounded in Standard Operational Procedures (SOPs), task-based interactions, and extensive listening practice featuring diverse accents. The paper contributes empirical evidence to the literature on needs analysis in ESP vocational education and offers practical recommendations for English teachers and curriculum developers in the Indonesian hospitality sector.